Colorectal Cancer: Pathogenesis and Targeted Therapy - Jingyuan Li; Jiashu Pan; Lisheng Wang; Guang Ji; Yanqi Dang (MedComm)
ABSTRACT Colorectal cancer (CRC) ranks among the most prevalent malignant neoplasms globally. A growing body of evidence underscores the pivotal roles of genetic alterations and dysregulated epigenetic modifications in the pathogenesis of CRC. In recent years, the reprogramming of tumor cell metabolism has been increasingly acknowledged as a hallmark of cancer. Substantial evidence suggests a crosstalk between tumor cell metabolic reprogramming and epigenetic modifications, highlighting a complex interplay between metabolism and the epigenetic genome that warrants further investigation. Biomarkers associated with the pathogenesis and metabolic characteristics of CRC hold significant clinical implications. Nevertheless, elucidating the genetic, epigenetic, and metabolic landscapes of CRC continues to pose considerable challenges. Here, we attempt to summarize the key genes driving the onset and progression of CRC and the related epigenetic regulators, clarify the roles of gene expression and signaling pathways in tumor metabolism regulation, and explore the potential crosstalk between epigenetic events and tumor metabolic reprogramming, providing a comprehensive mechanistic explanation for the malignant progression of CRC. Finally, by integrating reliable targets from genetics, epigenetics, and metabolic processes that hold promise for translation into clinical practice, we aim to offer more strategies to overcome the bottlenecks in CRC treatment.